REFORMULASI ZIJ AL-SULṬĀN ULUGH BEK DALAM MENENTUKAN AWAL BULAN KAMARIAH DI INDONESIA - Abdul Kohar; Sofyan, Muhammad Saleh (ELFALAKY: Jurnal Ilmu Falak, 2025)
Zij al-Sulṭān Ulugh Bek is a 15th century astronomical catalogue, one of the zijs used as an important reference to determine important times in the Hijri calendar for Muslims in Indonesia, such as the beginning of Ramadan and Eid al-Fitr. However, despite its great historical value, Zij al-Sulṭān needs to be updated and adjusted to current conditions and developments in Astronomy. Comparison of the results of Hisab Awal Bulan Kamariah with contemporary hisab and Nurul Anwar's true hisab reveals that Zij al-Sulṭān has good accuracy, but there is a difference in the ijtimak time and the height of the crescent moon in a few minutes. Therefore, to improve accuracy, corrections and adjustments need to be made according to geographical differences, more modern astronomical calculations, and the use of sophisticated astronomical equipment and software. This study provides an alternative calculation to develop Zij al-Sulṭān to have better accuracy as a hisab for determining the beginning of the lunar month in Indonesia.